The use of telepsychiatry within forensic practice: a literature review on the use of videolink: a ten-year follow-up - Sales, Christian P.; McSweeney, Leo; Saleem, Younus; Khalifa, Najat (Taylor & Francis, 2017)
In the last decade, telepsychiatry – the use of telecommunications technologies to deliver psychiatric services from a distance – has been increasingly utilised in many areas of mental health care. Since the review by Khalifa and colleagues in 2007 the body of literature relevant to the forensic applications of telepsychiatry has grown substantially, albeit not by much in the United Kingdom. In the current review, we aim to provide an update summary of the literature published since 2007 to determine the effectiveness and feasibility of increasing telepsychiatry utilisation in forensic practice. The literature reviewed provides some encouraging evidence that telepsychiatry is a reliable, effective and highly acceptable method for delivering mental health care in forensic settings. There are also a number of papers that indicate the use of telepsychiatry may be cost effective for health providers in the longer term. Further research is required to consider the potential legal and ethical implications of using telepsychiatry in forensic settings.